CODE MIXING AND CODE SWITCHING PHENOMENON IN AḤBABTUKA AKŚARA MIN MĀ YANBAGĪ NOVEL: A SOCIOLINGUISTIC STUDY - Abdul Jawat Nur (CMES (Center of Middle Eastern Studies), 2021)
This paper will describe the phenomenon of code mixing and code switching in Aḥbabtuka Akśara Min Mā Yanbagī's novel based on sociolinguistic studies. The phenomenon of code mixing and code switching in this novel is worth further investigation because the novel makes extensive use of code mixing and code switching.. In addition, code mixing and code switching in Aḥbabtuka Akśara Min Mā Yanbagī's novel has not been discussed by other researchers. Based on the research that has been done, it is concluded that the code mixing in the novel Aḥbabtuka Akśara Min Mā Yanbagī is in the form of words and phrases. The form of code-mixing found is code-mixing of English words and phrases. The most widely used code switching is internal code switching and external code switching. Internal code switching occurs from Fuṣḥā Arabic to Amiyah Arabic and back to Fuṣḥā Arabic. In addition, external code switching occurs from Arabic Fuṣḥā to English and back again to Arabic Fuṣḥā. The factors that cause code mixing in Aḥbabtuka Akśara Min Mā Yanbagī's novel (2014) by Aṡīr 'Abdullāh are (a) bringing up humor, (b) appreciation for the interlocutor, (c) petition to the interlocutor, and (d) annoyance. The factors that cause code switching are (a) the attitude of the speaker, and (b) the expression of the speaker's solidarity with the group.